P797 Antibody response to mycoplasma genitalium in longitudinally infected men with non-gonococcal urethritis. (14th July 2019) - Wood, Gwendolyn; Cabral, Stefanie Iverson; Manhart, Lisa; Lowens, Sylvan; Gillespie, Catherine; Totten, Patricia
Abstract : Background: A sensitive and specific serologic test is needed to evaluate the association of Mycoplasma genitalium (MG) infection with serious upper reproductive tract sequelae in women. In this study, we compared the ability of immunoblot and ELISA methods to detect serum antibody reactivity with the immunodominant MgpB and MgpC adherence proteins among MG-infected men with nongonococcal urethritis (NGU). Methods: Serum samples collected at two time points (spanning 15–86 days) from 22 MG-infected, PCR-positive men with NGU were assayed for reactivity to MG whole cell lysates by immunoblot, and to the conserved C-terminus of MgpB by ELISA, compared to 19 MG-negative controls. Additionally, we selected six MG(+) men with a variety of immunoblot reactivities and examined their serum specimens for ELISA reactivity to 16 recombinant peptides spanning conserved and variable domains of MgpB and MgpC at two time points. Results: Among men with current MG infection, immunoblot detection of MgpB antibodies outperformed an ELISA assay detecting reactivity to the conserved C-terminus of MgpB with 90.9% and 81.8% sensitivity, and 92.3% and 82.3% specificity, respectively. In contrast to immunoblot results, ELISA-reactivity to individual peptides spanning MgpB and MgpC indicated patient antibodies more frequently targeted the C-terminus of MgpC than the C-terminus of MgpB. As expected, most patient sera reacted poorly in ELISAs to recombinant peptides spanning the MgpB and MgpC variable regions as these sequences corresponded to the G37 type strain rather than the infecting strains. Conclusion: Our findings suggest that an MG ELISA test could be improved by including conserved portions of both the MgpB and MgpC proteins, providing an alternative to the more labor intensive immunoblot. Such a test will be especially valuable for associating current or past MG infection with serious upper reproductive tract disease in women. Disclosure: No significant relationships.